Glow - Bryant, Megan E. (Albert Whitman and Company, 2018)
After financial troubles hit her family, Julie decides to sacrifice her college fund in order to save their home, resigning herself to working a part-time job until she saves up more. One day at a thrift store, Julie discovers a set of old paintings. Buying them, she returns home, hangs it up, and turns off the lights to go to sleep, only to discover a secret picture painted in glow-in-the-dark material light up. Julie delves into the life of the artist and learns more about the real-life Radium Girls of World War I. She also stumbles upon a love story, and a mystery that's remained unsolved for decades.